(untitled) (Journal of Hama University, 2020)
-This study aims at the following: To identify the levels of social anxiety in deaf students and its relation to sex, age and the hearing status of their parents -The study sample consisted of 35 male and female students in the special education for the deaf institute in Damascus city. -To achieve the goals of the study, the researcher used the Wahid Kamal Mustafa (2003) social anxiety scale -The study showed the following results: 1) There are strong statistically significant differences in the average scores of the study sample in the social anxiety scale due to the variable of gender, in which Females scored the highest. 2) 1) there are strong statistically significant differences in the average scores of the study sample in the social anxiety scale due to the variable of age, in which the age group (13-17) years scored the highest. 3) 1) there are strong statistically significant differences in the average scores of the study sample in the social anxiety scale due to the variable of the hearing status of their parents (Deaf- Normal hearing), in which hearing parents scored the highest.